Determining near saturated soil hydraulic properties at oil palm plantation using wooding equation and inverse solution [electronic resources] - Nor Suhada Abd. Rashid, 1987- (2012)
Thesis (Sarjana Kejuruteraan (Awam - Hidraul dan Hidrologi)) - Universiti Teknologi Malaysia, 2012